THE ROLE OF STAFF DEVELOPMENT IN ORGANISATIONS - SHONHIWA, DOCTOR CAXTON (IJRDO- Journal of Educational Research, 2017)
This paper offers suggestions and tools for employees and their supervisors to help employeesachieve greater success in their current position and plan for career advancement. The paperargues that a skilled and knowledgeable workforce positively impacts organisationalperformance. Employee development should be a shared responsibility which requirescollaboration between the employee and supervisor. The supervisor’s role as a performancecoach includes such activities as clarifying performance and behavioural expectations, helpingemployees understand the organization as a whole, helping employees understand theorganisations’ long and short-term goals, identifying learning opportunities, giving positive andconcrete feedback and providing necessary resources. In addition to meeting currentperformance expectations, employees must be able to adapt to meet evolving organisationalneeds. For example, new skills and knowledge are often required to keep pace withtechnological change and new departmental procedures. The attainment of knowledge, skills andabilities can be achieved in numerous ways; many at no or low cost within the organisation.